Hafnia alvei Urosepsis in a Kidney Transplant Patient - Mario Stanic; Edgar Meusburger; Gabriele Hartmann; Karl Lhotta (Case Reports in Transplantation)
Hafnia alvei, a gram-negative facultative anaerobic, rod-shaped bacterium, is a rare cause of infection in humans. We report on a renal transplant patient who developed H. alvei pyelonephritis and urosepsis. The source of infection remains enigmatic but is most likely the intestinal tract. Appropriate antibiotic therapy with cefepime followed by oral ciprofloxacin brought about rapid resolution of symptoms and complete recovery. H. alvei may cause severe infection in transplant patients without predisposing factors such as hospitalization, invasive procedures, or antibiotic treatment.